2021
DOI: 10.1021/acs.jafc.1c01822
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of HO1 3′UTRs by Alternative Polyadenylation Suppresses Adipogenesis in 3T3-L1

Abstract: Appropriately increasing intramuscular fat content can help improve meat quality, so it is necessary to explore the internal molecular mechanism of preadipocyte differentiation. The role of heme oxygenase 1 (HO1) in cell oxidative stress, energy metabolism, cell proliferation, and differentiation has gradually been revealed. Here, we used 3′RACE to identify the full-length 3′ untranslated region (3′UTR) of HO1 and found that a very short 3′UTR variant was produced by alternative polyadenylation (APA). HO1 with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 35 publications
(61 reference statements)
1
7
0
Order By: Relevance
“…In this study, it was demonstrated that the upregulation of the short isoform of ME1 is more significant than that of the long isoform. Our results are consistent with previous findings on the expression of short APA isoforms of AAMDC, HO1, MCL1, and STAT5B . However, studies have also revealed that the upregulation of long APA isoforms of some genes is more significant, which also reflects the complexity of APA in posttranscriptional regulation .…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, it was demonstrated that the upregulation of the short isoform of ME1 is more significant than that of the long isoform. Our results are consistent with previous findings on the expression of short APA isoforms of AAMDC, HO1, MCL1, and STAT5B . However, studies have also revealed that the upregulation of long APA isoforms of some genes is more significant, which also reflects the complexity of APA in posttranscriptional regulation .…”
Section: Discussionsupporting
confidence: 93%
“…Studies have revealed that the short 3′ UTR-APA isoform of several genes is at least partially attributed to escaping miRNAs regulation leading to higher expression levels, thus affecting different biological processes, such as AAMDC and HO1 in adipocytes, , Pax3 in muscle stem cells, K i -67, PolH, and FNDC3B in cancer cells, and MCL1 and CD5 in activated T cells. , Therefore, we hypothesized that the differential expression of the 3′ UTR-APA isoforms of ME1 might be related to the regulation of their cross-talk with the corresponding miRNAs. Interestingly, in silico analysis revealed that only three conserved miRNAs could target the 3′ UTR of ME1, and all of them targeted exclusive regions of the long 3′ UTR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative polyadenylation generates transcripts with different 3′ UTR length. During adipogenesis, a trend towards longer 3′ UTR was discovered [ 119 ], which makes them more or less susceptible to the binding of miRNAs or RBPs, thereby affecting adipogenesis [ 46 , 120 , 121 ]. In addition, over 100 post-transcriptional modifications, such as N6-methyladenosine (m6A), 5-methylcytidine, and inosine, have been found in RNAs [ 122 ].…”
Section: Concluding Remarks and Future Perspectivementioning
confidence: 99%
“…Moreover, APA events have been associated with tail fat deposition in sheep (Yuan et al 2021b ). Furthermore, while APA-induced truncation of heme oxygenase 1 (HO1) 3′ UTR has a strong inhibitory effect on preadipocyte differentiation of 3T3-L1 cells (Cui et al 2021 ), 3′ UTR shortening of the adipogenesis-associated Mth938 domain containing (AAMDC) protein has a positive effect on the differentiation process of bovine preadipocytes (Xiao et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%